A systematic and bibliometric review of the audit quality in the public sector (International Journal of Business Innovation, 2022)
This document includes a systematic and bibliometric review of research outcome addressing the quality of public sector review published between 1991 and 2021. The methodology followed for systematic review foresees the use of the analysis protocol. As far as bibliometric analysis is concerned, we try to direct readers to identify the most important research, if any, and we analyse any references also in the aspect of reciprocity. The audit quality has been studied mainly in the private sector, in the public sector there are relatively few reference texts and there do not seem to be many relationships and integrations between the texts taken to reference. An efficient public audit quality can bring benefits to the population, which should consider this issue in theregulatory and institutional context as well as those who work in this field. Since this article still lacks, it contributes to literature by providing a theoretical picture of the different approaches used in the “analysis of this matter”. The framework explains that different approaches are followed to analyse audit quality in the public sector.
Keywords: audit quality; public sector; public administration; systematic review; bibliometric